African trypanosome strategies for conquering new hosts and territories: the end of monophyly? - Lukeš, Julius; Kachale, Ambar; Votýpka, Jan; Butenko, Anzhelika; Field, Mark C (Trends in parasitology, 2022)
Trypanosoma brucei parasites are the causative agents of African trypanosomiasis in humans, as well as surra, nagana, and dourine in animals. According to current widely used nomenclature, T. brucei is a group of five (sub)species, each causing a distinct disease and possessing unique genetic marker(s) or a combination thereof. However, minimal nuclear genome differences, sometimes accompanied by ongoing genetic exchange, robustly support polyphyly resulting from multiple independent origins of the (sub)species in nature. The ease of generating such (sub)species in the laboratory, as well as the case of overlapping hosts and disease symptoms, is incompatible with the current (sub)species paradigm, which implies a monophyletic origin. Here, we critically re-evaluate this concept, considering recent genome sequencing and experimental studies. We argue that ecotype should be used going forward as a significantly more accurate and appropriate designation.
Keywords: Trypanosomiasis; parasitism; trypanozomiáza; speciation; diversity; population structure; Animals; Humans; Trypanosomiasis, African; evolution; lidé; zvířata; Trypanosoma brucei brucei; Trypanosoma; trypanozomóza africká